Retrospective Comparison of Radial and Femoral Access in Coronary Interventions - Khan, Farhat Ullah; Afzal, Zeeshan; Akhtar, Syed Ahsan; Ayub, Asfandyar; Hafeez, Muhammad (Indus Journal of Bioscience Research, 2025)
Introduction: Percutaneous coronary interventions (PCI) remain a debatable choice of access site. Procedural success, complications, and recovery outcomes in terms of the impact of complications were shown to be lower for radial access when compared to femoral access. However, comparative outcomes in terms of procedural success require further evaluation. Objective: To compare the outcomes of radial and femoral access in PCI settings with respect to procedural success, complications, and patient recovery. Materials and Method: This retrospective cohort study conducted at Department of Cardiology, Hayatabad Medical Complex, Peshawar from July, 2022 to December, 2022. Five hundred patients undergoing PCI were analyzed, and data were compared regarding procedural success, complications, and recovery outcomes between radial and femoral access. Results: Fewer complications, such as bleeding and hematoma, and shorter hospital stays were found with radial access. However, the groups had no significant differences in major adverse cardiac events. Conclusion: Femoral access is safer and more convenient for PCI, but it has more complications and slower recovery compared to radial access.